Design and Development of Wireless Stakeout System based on ZigBee Transceiver Modules - SARWAR, MUHAMMAD BILAL (2016)
Wireless technology has become a new emerging technology in stakeout and security concerned industries. Study of robot communication with energy efficiency is also one of the important research area. Therefore